QUALITY OF LIFE OF PEOPLE WHO PRACTICE BALLROM DANCE - Zenite Machado; Gabriella Roberta dos Santos; Adriana Coutinho de Azevedo Guimarães; Sabrina Fernandes; Amanda Soares (Revista Brasileira de Atividade Física e Saúde)
The transversal cut study aimed to investigate the quality of life in ballroom dancepractitioners in Florianopolis – SC. The sample was composed of 402 subjects aged 21to 83 years, who use to attend ballroom dance classes. In order to perform the study,a questionnaire was carried out, which consists of four parts: personal identifi cation,socioeconomic status, dance practice and quality of life (assessed by means ofthe WHOQOL BREF Questionnaire). After carrying the study out it is observed thatballroom dance is searched by individuals in diff erent ages, particularly the youngerunmarried ones belonging to an upperclass. Ballroom dance seems to be an instrumentfor improving/managing quality of life on the four diff erent domains (physical,psychological, social and environmental). By means of Spearman’s correlation thequality of life domain are associated to certain characteristics from which the mostrelevant were the participation in another activity (physical, psychological, social andenvironmental), the age (physical and environmental), the practice time (physical andsocial), and aspects of ballroom dance practice (physical). Furthermore, associationsbetween physical, social, and environmental domains were found. The psychologicaldomain is associated with the social one, and the environmental, is also associated withthe psychological and social domains.